Deprehensio Financial Statement Fraud: Mengungkapkan Kecurangan Melalui Sudut Pandang Heptagon Model - Silpian Jian Linia Wati; Shinta Permata Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Fraud is a deceptive act committed with the intent of obtaining unlawful gain. This study aims to analyze the influence of the fraud heptagon—comprising the elements of pressure, opportunity, rationalization, arrogance, competence, culture, and religiosity—on financial statement fraud in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period, using the Beneish M-Score model. The sample in this study consists of 50 companies or 150 data points selected using purposive sampling. The research data are secondary data obtained from the companies’ annual reports. The results of this study indicate that rationalization influences financial statement fraud, whereas pressure, opportunity, arrogance, competence, culture, and religiosity do not influence financial statement fraud. This study is expected to provide information regarding the factors that trigger fraud and assist in detecting fraud in financial statements. Additionally, this study can serve as a reference for auditors to enhance their role in assessing the fairness and appropriateness of financial statement presentation.